Evangelische Erziehungsverantwortung Eine religionspädagogische Untersuchung zum Werk Friedrich Delekats (1892-1970) - Simojoki, Henrik (Mohr Siebeck, 2008)
Protestant Responsibility for Education. A Study of Friedrich Delekats (1892-1970) Works from the Perspective of the Theory of Religious Education.
PublicationDate: 20240123
Keywords: Religionspädagogik -- Erziehungsverantworung -- Delekat, Friedrich -- Kirchengeschichte -- Praktische Theologie -- Array